Negative active material, negative pole piece, secondary battery and electric equipment

By adjusting the activity density of edge defects in the carbon coating layer, the anisotropy ratio of graphite microcrystals, and the particle size distribution of powder, the microstructure parameters of the anode active material were optimized, achieving high capacity retention and low expansion rate of lithium-ion batteries during high-rate charging, thus solving the performance bottleneck of graphite anode materials in the existing technology.

CN120914231APending Publication Date: 2025-11-07ZHEJIANG ZEEKR INTELLIGENT TECH CO LTD +2

Patent Information

Application Number
CN202511082994.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-04
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

Existing lithium-ion battery anode materials suffer from low ion migration rate, easy structural expansion, interface runaway risk, and thermal safety boundary challenges during high-rate charging, making it difficult to achieve excellent fast charging and cycle performance in mass production.

Method used

By adjusting the activity density of edge defects in the carbon coating layer, the anisotropy ratio of graphite microcrystals, and the particle size distribution of powder, a composite performance index (CPI) is defined, and the microstructural parameters of the negative electrode active material are optimized to achieve a synergistic improvement in fast charging and long cycle performance.

Benefits of technology

Under 4C fast charging conditions, the capacity retention rate of the anode material is higher than 85%, and the electrode expansion rate is controlled within 17.1%, which has good prospects for production and application and solves the performance bottleneck of graphite anode materials in the existing technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120914231A_ABST
    Figure CN120914231A_ABST
Patent Text Reader

Abstract

The invention discloses a negative electrode active material, a negative electrode plate, a secondary battery and electric equipment, and belongs to the related technical field of secondary batteries, the negative electrode active material comprises a graphite inner core and a carbon coating layer covering at least part of the surface of the graphite inner core; the comprehensive performance parameter of the negative electrode active material is CPI; the value of the CPI meets the following relational expression: 0.7 < = CPI < = 3.64. According to the negative electrode active material design scheme provided by the invention, a composite performance index (CPI) is innovatively defined by constructing a collaborative regulation model of three key structure parameters, namely, a carbon coating layer edge defect active density (WD4 / WG), a graphite microcrystal anisotropy ratio (La / Lc) and a powder particle size distribution span (Span). Through research, when the CPI of the material meets the following interval condition: 0.7 < = CPI < = 3.64, the material has good fast charge and cycle performance and has good production and application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of secondary batteries, in particular to a negative electrode active material, a negative electrode sheet, a secondary battery and an electric device. BACKGROUND

[0002] In recent years, the global power battery industry has shown an explosive growth trend. Driven by this, downstream application scenarios have higher requirements for the comprehensive performance of batteries, among which the electrochemical performance of electrode materials, including key indicators such as fast charging capability and cycle performance, is more demanding.

[0003] In commercialized lithium-ion battery systems, artificial graphite as the mainstream negative electrode material, although has a theoretical specific capacity of 372 mAh / g and a mature graphitization process system, still gradually shows technical bottlenecks in extreme application scenarios, specifically manifested as:

[0004] 1) Ion transport kinetics shackles: the narrow interlayer spacing of 0.335 nm of the graphite (002) crystal plane forms a natural lithium ion migration barrier, resulting in a significantly lower effective ion migration rate than the theoretical value during high-rate charging. This interlayer diffusion limitation directly restricts the high-power output characteristics of the battery, which is particularly significant in electric vehicle fast charging scenarios.

[0005] 2) Structural degradation mechanism: the layered graphite structure relying on van der Waals forces is prone to co-intercalation of solvent molecules during repeated intercalation and deintercalation of lithium ions. Experimental data shows that the graphite interlayer expansion rate exceeds 15% after 300 cycles, causing the active material and the current collector contact resistance to increase by more than 40%, which is the main cause of capacity attenuation.

[0006] 3) Interface out-of-control risk: under fast charging conditions, electrode polarization intensifies, causing local potential to approach the lithium deposition critical value (-0.08V vs. Li + / Li), triggering non-uniform lithium deposition to form dendrites. Simultaneous characterization found that the solid electrolyte interface film (SEI) abnormally thickened at a rate of >3 nm / week, causing the active lithium loss rate to increase by more than 3 times.

[0007] 4) Thermal safety boundary challenge: the Joule heating effect generated by high-rate charging and discharging causes the battery temperature to rise by more than 25K, and when the working temperature reaches 45℃, the lithium deposition reaction kinetics barrier on the surface of graphite is reduced by 60%, significantly increasing the risk of thermal runaway.

[0008] The prior art scheme (such as CN114824226A) optimizes the parameter combination of the carbon coating layer thickness, the pole piece porosity and the specific surface area, and although the rate performance is improved under laboratory conditions, the improvement scheme has essential limitations: the accurate control of the above parameters highly depends on high-end characterization equipment such as transmission electron microscopy (TEM), and a multi-dimensional parameter correlation model needs to be established, which is difficult to realize process closed-loop control in large-scale production, resulting in limited practical production application value.

[0009] Therefore, it is of great significance to develop a negative electrode active material that has good fast charging and cycling performance and is expected to be used in actual production. SUMMARY

[0010] The present application aims to at least solve one of the technical problems existing in the prior art. To this end, the present application proposes a negative electrode active material that has good fast charging and cycling performance and good production application prospects.

[0011] The present application also proposes a negative electrode pole piece prepared from the above material.

[0012] The present application also proposes a secondary battery prepared from the above material or negative electrode pole piece.

[0013] The present application also proposes an electric device prepared from the above material, negative electrode pole piece or secondary battery.

[0014] According to a first aspect of the present application, a negative electrode active material is provided, comprising a graphite core and a carbon coating layer covering at least part of the surface of the graphite core.

[0015] The negative electrode active material has a carbon characteristic peak in the Raman spectrum, and the carbon characteristic peak includes a D4 peak with a peak shift of 1160-1200 cm -1 and a G peak with a peak shift of 1560-1600 cm -1 after peak separation processing, the half-height width of the D4 peak is W D4 , and the half-height width of the G peak is W G .

[0016] The average planar stacking width of the negative electrode active material is La, and the average side stacking height is Lc.

[0017] The particle size distribution span of the negative electrode active material is S.

[0018] The comprehensive performance parameter of the negative electrode active material is CPI.

[0019] The W D4 , W G , La, Lc, S and CPI satisfy the following relationship: CPI = (W D4 / W G ).0.55 x (La / Lc) x (S / 0.65) 0.35

[0020] The value of the CPI satisfies the following relationship: 0.7 ≤ CPI ≤ 3.64.

[0021] The negative electrode active material according to the embodiments of the present application has at least the following beneficial effects: the design scheme of the negative electrode active material proposed in the present application innovatively defines a composite performance index (CPI = (W D4 / W G ) D4 x (La / Lc) x (S / 0.65) G 0.55 ) by synergistically regulating a model of three key structural parameters: edge defect activity density (W 0.35 ) of the carbon coating layer, anisotropy ratio (La / Lc) of the graphite crystallites, and span (S) of the particle size distribution. Research has established that when the CPI of the material satisfies the following interval condition: 0.7 ≤ CPI ≤ 3.64, the following technical breakthroughs can be achieved: the capacity retention rate is still higher than 85% after 1000 charge-discharge cycles under 4C fast charging conditions, and at the same time, the expansion rate of the full-charged electrode sheet is controlled within 17.1%. Further, the above key parameters can be standardized characterized by conventional detection equipment in the battery industry (Raman spectrometer, X-ray diffractometer, and particle size analyzer, etc.), without the need for special sample preparation treatment or the regulation of parameters such as graphitization degree, specific surface area, powder OI value, sphericity, coating layer thickness, pore volume, and porosity of the active material, and thus have good production application prospects. The present application scheme establishes a quantitative mapping relationship between the microstructure parameters of the material and the macroscopic electrochemical performance, and designs a graphite negative electrode material that can achieve fast charging, low expansion, and long cycle life through multi-dimensional parameter synergy, successfully resolving the contradiction between ion transport kinetics and structural stability of the graphite negative electrode material, and providing a new technical path for developing the next generation of fast-charging battery negative electrode materials.

[0022] According to some specific embodiments of the present application, the value of the CPI satisfies the following relationship: 1.38 ≤ CPI ≤ 3.64.

[0023] According to some other specific embodiments of the present application, the value of the CPI satisfies the following relationship: 1.38 ≤ CPI ≤ 3.42.

[0024] According to some specific embodiments of the present application, the value of the CPI satisfies the following relationship: 1.58 ≤ CPI ≤ 3.64.

[0025] ​​According to some embodiments of the present application, the value of the CPI satisfies the following relationship: 1.58≤CPI≤3.42.

[0026] According to some embodiments of the present application, the value of the CPI satisfies the following relationship: 1.58≤CPI≤2.84.

[0027] According to some embodiments of the present application, the value of the CPI satisfies the following relationship: 1.8≤CPI≤3.64.

[0028] According to some embodiments of the present application, the value of the CPI satisfies the following relationship: 2≤CPI≤3.

[0029] According to some embodiments of the present application, the W D4 and the W G satisfy the following relationship: 0.3≤W D4 / W G ≤1.

[0030] According to some embodiments of the present application, the W D4 and the W G satisfy the following relationship: 0.6≤W D4 / W G ≤0.9.

[0031] According to some embodiments of the present application, the W D4 and the W G satisfy the following relationship: 0.65≤W D4 / W G ≤0.85.

[0032] According to some embodiments of the present application, due to the fact that the grain sizes are not exactly the same, the average value obtained by multiple measurements can better represent the crystallite parameter of the negative active material, i.e. the grain anisotropy ratio.

[0033] According to some embodiments of the present application, the multiple times are more than 3.

[0034] According to some embodiments of the present application, the multiple times are more than 10.

[0035] According to some embodiments of the present application, based on the multiple X-ray diffraction tests, the average value of the plane packing width is obtained by calculating the plane packing width based on the result of each test, respectively; wherein the formula for calculating the plane packing width according to the X-ray diffraction spectrum data is: plane packing width=kλ / (β (110) cosθ (110) ), wherein k is the Scherrer constant, λ is the wavelength of X-ray, β (110)FWHM (radian) of the diffraction peak of the (110) crystal face of the graphite carbon (110) is the diffraction peak angle corresponding to the (110) crystal face of the graphite carbon.

[0036] According to some embodiments of the present application, the Lc is obtained by averaging the side stacking height calculated based on the result of each test according to the multiple X-ray diffraction test; wherein the formula for calculating the side stacking height according to the X-ray diffraction spectrum data is: side stacking height = kλ / (β (002) cosθ (002) ), wherein k is the Scherrer constant, λ is the wavelength of the X-ray, β (002) FWHM (radian) of the diffraction peak of the (002) crystal face of the graphite carbon (002) is the diffraction peak angle corresponding to the (002) crystal face of the graphite carbon.

[0037] According to some specific embodiments of the present application, the value of k is 0.89. The value of k is related to the determination method of the full width at half maximum (FWHM), the grain shape and the particle size distribution, and is generally 0.87-1. Generally, when β represents the half width, k is 0.89.

[0038] According to some specific embodiments of the present application, the value of λ is determined by the radiation source of the X-ray spectrometer, and if the Cu target is used, the value of λ is (angstrom), for the convenience of calculation, it can also be rounded as needed, such as rounding to

[0039] According to some specific embodiments of the present application, the La and Lc satisfy the following relationship: 1.6≤La / Lc≤2.6.

[0040] According to some other specific embodiments of the present application, the La and Lc satisfy the following relationship: 1.8≤La / Lc≤2.4.

[0041] According to some embodiments of the present application, the formula for calculating the span of the particle size distribution is as follows: S = (D 90 -D 10 ) / D 50 , wherein D 90 represents the particle size of 90% in the cumulative particle size distribution based on the volume basis, D 10 represents the particle size of 10% in the cumulative particle size distribution based on the volume basis, and D 50 represents the particle size of 50% in the cumulative particle size distribution based on the volume basis.

[0042] According to some specific embodiments of the present application, the span of the particle size distribution satisfies the following relationship: 0.6≤S≤1.7.

[0043] According to some specific embodiments of the present application, the particle size distribution span satisfies the following relationship: 1≤S≤1.7.

[0044] According to some specific embodiments of the present application, the particle size distribution span satisfies the following relationship: 0.88≤S≤1.36.

[0045] According to some embodiments of the present application, the tap density of the negative active material is TD g / cm 3 .

[0046] According to some specific embodiments of the present application, the tap density satisfies the following relationship: 0.8≤TD≤1.2.

[0047] According to some specific embodiments of the present application, the tap density satisfies the following relationship: 0.85≤TD≤1.18.

[0048] According to some specific embodiments of the present application, the tap density satisfies the following relationship: 0.9≤TD≤1.18.

[0049] According to some specific embodiments of the present application, the tap density and the particle size distribution span satisfy the following relationship: TD≥1.1-0.15×S. The constraint relationship between TD and Span is established to ensure the compatibility of high tap density and particle size distribution of the material. When TD≥1.1-0.15×Span, the volume expansion of the negative electrode sheet and the lithium consumption in long cycle can be significantly reduced.

[0050] According to some embodiments of the present application, the Raman spectrum is further subjected to fitting processing after peak separation.

[0051] According to some specific embodiments of the present application, the fitting includes Gaussian fitting. Gaussian fitting is a commonly used fitting method in the art, and other fitting methods or no fitting can also be used.

[0052] According to some specific embodiments of the present application, the Raman spectrum includes a Raman spectrum subjected to refinement processing.

[0053] According to some specific embodiments of the present application, the X-ray diffraction spectrum includes a spectrum subjected to refinement processing.

[0054] The above structural characteristic parameters (W D4 , W G, La and Lc), due to the influence of Raman test and XRD test noise on the smoothness of the spectrum, in order to make the test data as smooth as possible, the field will generally be refined, which can be refined by using commonly used software in the field, such as origin (for XRD data, Jade can also be used), using the universal parameters in the field, without special adjustment.

[0055] According to some embodiments of the present application, the graphite includes at least one of natural flake, artificial graphite sheet, artificial graphite block and artificial graphite ball. The specific type or source of the graphite core is not limited, and various known graphite materials such as traditional natural graphite and artificial graphite can be used.

[0056] According to some embodiments of the present application, the carbon coating layer is an amorphous carbon coating layer.

[0057] According to some specific embodiments of the present application, the carbon coating layer contains at least one of hard carbon and soft carbon.

[0058] According to some embodiments of the present application, the precursor of the carbon coating layer includes at least one of coal tar pitch, tar pitch, medium temperature coal tar pitch, high temperature coal tar pitch, medium temperature oil tar pitch, high temperature oil tar pitch, phenolic resin, citric acid, glucose and soluble starch.

[0059] According to the second aspect of the present application, a negative electrode sheet is provided, which includes a current collector and a coating layer arranged on at least one side surface of the current collector, and the raw material for preparing the coating layer includes the above-mentioned negative electrode active material.

[0060] According to some embodiments of the present application, the preparation method of the negative electrode sheet includes the following steps:

[0061] Mixing the negative electrode active material, the conductive agent, the thickening agent, the binder, the toughening agent and water to prepare a negative electrode slurry;

[0062] Coating the negative electrode slurry on at least one side surface of the negative electrode current collector, drying and rolling to obtain the negative electrode sheet.

[0063] According to some specific embodiments of the present application, the mass fraction of the negative electrode active material, the conductive agent, the thickening agent, the binder and the toughening agent is 96-98, 0.1-1, 0.8-1.8, 0.5-1.5 and 0.1-1, respectively.

[0064] According to some specific embodiments of the present application, the preparation method further includes the step of die cutting after rolling.

[0065] According to some embodiments of the present application, the negative electrode slurry has at least one of the following characteristics:

[0066] 1) the solid content of the negative electrode slurry is 30-65 wt.%;

[0067] 2) the viscosity at room temperature is 1000-8000 mPa-s, and the room temperature is 25±2℃.

[0068] According to some embodiments of the present application, the coating layer has at least one of the following characteristics:

[0069] 1) the single-side thickness of the coating layer is 0.05-0.30 mm;

[0070] 2) the mass per unit area of the coating layer is 80-200 g / m 2 ;

[0071] 3) the compacted density of the coating layer is 1.30-1.75 g / cm 3 .

[0072] According to a third aspect of the present application, a secondary battery is provided, which comprises a positive electrode sheet, a negative electrode sheet, and a separator film, the separator film being located between the positive electrode sheet and the negative electrode sheet, and the negative electrode sheet is the above-mentioned negative electrode sheet.

[0073] According to a fourth aspect of the present application, an electric device is provided, which comprises the above-mentioned secondary battery.

[0074] According to some embodiments of the present application, the electric device is an electric vehicle. It can also be other electric devices such as energy storage systems, electric tools, unmanned aerial vehicles, mobile devices such as wearable products, laptops, mobile phones, etc.

[0075] According to some specific embodiments of the present application, the electric device is an electric car or an electric bicycle. It can also be other electric vehicles such as electric motorcycles, electric scooters, electric wheelchairs, etc.

[0076] Additional aspects and advantages of the present application will be in part apparent and in part pointed out hereinafter. BRIEF DESCRIPTION OF DRAWINGS

[0077] Figure 1 is a structural schematic diagram of a negative electrode active material of an embodiment of the present application and a schematic diagram of the results of characterization of part of the structure parameters: specifically, Figure (a) is a structural schematic diagram of the negative electrode active material; Figure (b) is a schematic diagram of the results of Raman spectrum peak fitting; and Figure (c) is a schematic diagram of the crystallite parameters of the negative electrode active material.

[0078] Figure 2 is a scanning electron microscope characterization result diagram of the negative electrode active material of Example 1 of the present application.

[0079] Figure 3 is a Raman spectrum characterization result graph of the negative electrode active material of Example 1 of the present application.

[0080] Figure 4 is a XRD characterization result graph of the negative electrode active material of Example 1 of the present application.

[0081] Figure 5 is a laser diffraction particle size analyzer characterization result graph of the negative electrode active material of Example 1 of the present application.

[0082] Figure 6 is a lithium extraction test result graph of the lithium ion battery of Example 1 of the present application.

[0083] Figure 7 is a lithium extraction test result graph of the lithium ion battery of Comparative Example 1 of the present application.

[0084] In the drawings, the letter meaning is explained: D4: D4 peak fitting curve; D1: D1 peak fitting curve; D3: D3 peak fitting curve; G: G peak fitting curve; La: average plane stacking width; Lc: average side stacking height. DETAILED DESCRIPTION

[0085] The concept and the technical effects produced by the present application will be described below in conjunction with the embodiments, so as to fully understand the purpose, features and effects of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, but not all the embodiments. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present application. The test methods used in the embodiments are conventional methods unless otherwise specified. The materials, reagents, etc. used are commercially available unless otherwise specified. The same parameter values are used in the same parameter in each embodiment unless otherwise specified. The embodiments described below are exemplary and are used to explain the present application, and cannot be understood as limiting the present application.

[0086] In the description of the present application, the description of the terms "one embodiment", "some embodiments", "illustrative embodiment", "example", "specific example", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In the present specification, the illustrative description of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0087] As described in the background of the present application, in the current commercialized negative electrode material system of lithium ion batteries, graphite-based materials dominate the global negative electrode material market due to their mature preparation process and considerable theoretical specific capacity. However, the cycle life of graphite-based negative electrode materials still needs to be further improved under fast charging conditions. The embodiments of the present application obtain fast-charging long-cycle graphite negative electrode materials by regulating the interface of active material powder, intrinsic body microcrystalline parameters and macroscopic indicators.

[0088] In the description of the present application, the planar stacking width refers to the grain size in the a-axis direction, and the side surface stacking height refers to the stacking height in the c-axis direction.

[0089] In the description of the present application, the full-width at the half of the maximum (FWHM) is also referred to as the half-peak width.

[0090] In a typical embodiment of the present application, a negative electrode active material is provided, which comprises a graphite core and a carbon coating layer covering at least part of the surface of the graphite core. The negative electrode active material has a carbon characteristic peak in the Raman spectrum, and after peak separation processing, the carbon characteristic peak includes a D4 peak with a peak shift of 1160-1200 cm -1 and a G peak with a peak shift of 1560-1600 cm -1 . The half-width of the D4 peak is W D4 , and the half-width of the G peak is W G . The average planar stacking width of the negative electrode active material is La, and the average side surface stacking height is Lc. The particle size distribution span of the negative electrode active material is S. W D4 , W G , La, Lc and S satisfy the following relationship: CPI = (W D4 / W G ) 0.55 × (La / Lc) × (S / 0.65) 0.35 , and the value of CPI satisfies the following relationship: 0.7 ≤ CPI ≤ 3.64.

[0091] Further, the inventors of the present application unexpectedly found that when the comprehensive performance parameter of the negative electrode active material is defined as CPI (CPI = (W D4 / W G ) 0.55 × (La / Lc) × (S / 0.65) 0.35 ) and the value of CPI satisfies the following relationship: 0.7 ≤ CPI ≤ 3.64, the electrochemical performance of the negative electrode active material is excellent, and the comprehensive performance of the negative electrode sheet and lithium ion battery prepared from the negative electrode active material is excellent, which can simultaneously have high fast-charging performance and long cycle performance.

[0092] In the present application, the so-called "coating" is not limited to direct coating, but also includes indirect coating. For example, when the carbon coating layer is directly attached to the surface of the graphite substrate, it is defined as a direct coating form; if there is a functional transition layer (such as a conductive polymer layer or an inorganic nanoparticle layer, etc.) at the interface between the two, it constitutes an indirect coating form. Based on factors such as interfacial bonding strength and charge transport efficiency, the direct coating form is preferred.

[0093] Further, the above-mentioned carbon coating layer covers at least part of the surface of the graphite core, and its form includes complete coating (i.e. completely encapsulating the core) or partial coating (i.e. covering only part of the surface). This coating structure can effectively protect the graphite core, thereby enhancing the structural stability of the negative electrode material and improving its fast-charging performance and cycle performance.

[0094] Figure 1 (a) shows the structural schematic diagram of the negative electrode active material provided by an embodiment of the present application. In order to characterize the defect characteristics of the carbon coating layer of the material, the material is tested by using Raman spectrum analysis technology, and the peak fitting result is shown in Figure 1 (b). The Raman spectrum of the graphitized carbon material presents D peak system and G peak, wherein the D peak system represents the existence of defect structure in the carbon material, and the G peak represents the existence of graphitized structure. The Raman spectrum is processed by refining, and the refined curve is obtained, and then the refined curve is processed by peak fitting, and is labeled in order of increasing characteristic peak frequency as: D4 peak fitting curve (~ 1160-1200 cm -1 ), D1 peak fitting curve (~ 1380 cm -1 ), D3 peak fitting curve (~ 1510 cm -1 ) and G peak fitting curve (~ 1560-1600 cm -1 ). Among them, the D peak system is related to the vibration mode of the defect of the carbon material, and the G peak corresponds to the characteristic vibration of the graphitized structure, and the activity density of the edge defect of the carbon layer can be quantitatively evaluated by the area ratio of each peak. In order to further analyze the microcrystalline parameters of the material, X-ray diffraction (XRD) characterization analysis is simultaneously carried out, and the microcrystalline parameters are calculated according to the XRD characterization results, Figure 1 (c) shows the meaning of the microcrystalline parameters: La represents the average grain size of the carbon microcrystalline along the a-axis direction (i.e. the plane stacking width, corresponding to the (110) crystal face direction), and Lc represents the average side stacking height along the c-axis direction (i.e. the side stacking height, corresponding to the (002) crystal face direction). These two parameters are calculated by plane stacking width = kλ / (β (110) cosθ (110) ) or side stacking height = kλ / (β (002) cosθ (002) ), and the average value obtained after calculation according to the characterization results of XRD can effectively characterize the anisotropy characteristics of the microcrystalline structure of the carbon material.

[0095] Exemplarily, in the present application, the value of CPI can be any one of 0.7, 0.72, 0.74, 0.76, 0.78, 0.8, 0.82, 0.84, 0.86, 0.88, 0.9, 0.92, 0.94, 0.96, 0.98, 1.0, 1.02, 1.04, 1.06, 1.08, 1.09, 1.1, 1.12, 1.14, 1.16, 1.18, 1.2, 1.22, 1.24, 1.26, 1.28, 1.3, 1.32, 1.34, 1.36, 1.38, 1.39, 1.4, 1.42, 1.44, 1.46, 1.48, 1.5, 1.52, 1.54, 1.56, 1.58, 1.6, 1.62, 1.64, 1.66, 1.68, 1.7, 1.72, 1.74, 1.76, 1.78, 1.8, 1.82, 1.84, 1.85, 1.86, 1.88, 1.9, 1.92, 1.94, 1.96, 1.97, 1.98, 2.0, 2.02, 2.04, 2.06, 2.08, 2.1, 2.12, 2.13, 2.14, 2.16, 2.18, 2.2, 2.22, 2.24, 2.26, 2.27, 2.28, 2.3, 2.32, 2.33, 2.34, 2.36, 2.38, 2.4, 2.42, 2.44, 2.46, 2.48, 2.5, 2.52, 2.54, 2.56, 2.58, 2.6, 2.62, 2.64, 2.66, 2.68, 2.7, 2.72, 2.74, 2.76, 2.78, 2.8, 2.82, 2.84, 2.86, 2.88, 2.9, 2.92, 2.94, 2.96, 2.98, 3.0, 3.02, 3.04, 3.06, 3.08, 3.1, 3.12, 3.14, 3.16, 3.18, 3.2, 3.22, 3.24, 3.26, 3.28, 3.3, 3.32, 3.34, 3.36, 3.38, 3.4, 3.41, 3.42, 3.44, 3.46, 3.48, 3.5, 3.52, 3.54, 3.56, 3.58, 3.6, 3.62, 3.64, or a range value group formed by any two of them.

[0096] In some embodiments of the present application, the value of CPI satisfies the following relationship: 1.38≤CPI≤3.64.

[0097] In some embodiments of the present application, the value of CPI satisfies the following relationship: 1.38≤CPI≤3.64.

[0098] In some other specific embodiments of this application, the value of CPI satisfies the following relationship: 1.58≤CPI≤3.64.

[0099] In some other specific embodiments of this application, the value of CPI satisfies the following relationship: 1.58≤CPI≤3.42.

[0100] In some other specific embodiments of this application, the value of CPI satisfies the following relationship: 1.58≤CPI≤2.84.

[0101] In some other specific embodiments of this application, the value of CPI satisfies the following relationship: 1.8 ≤ CPI ≤ 3.64.

[0102] In some other specific embodiments of this application, the value of CPI satisfies the following relationship: 2≤CPI≤3.

[0103] In some specific embodiments of this application, W D4 With W G The following relationship must be satisfied: 0.3 ≤ W D4 / W G ≤1.

[0104] For example, in this application, W D4 / W G The values ​​can be 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.5, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.6, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0 The range of values ​​consisting of any one or any combination of the following values: 0.67, 0.68, 0.69, 0.7, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.8, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.0.

[0105] The inventors of this application unexpectedly discovered during the material development and design process that the edge defect activity parameter W of carbon-coated graphite anode materials... D4 / W Gis the core index affecting the loss of cycle capacity. This parameter reflects the active density of edge defects of the carbon coating layer, and by regulating this parameter, sp 3 Hybrid carbon-based disordered microporous / mesoporous structure can achieve the following performance improvement: while improving the lithium intercalation kinetics, the active lithium loss rate is slowed down by optimizing the structural stability; when the active site distribution is more reasonable, the occurrence of side reactions under high temperature conditions can be effectively inhibited, which improves the capacity retention rate of the full battery during high-temperature cycling and prolongs the calendar life. This structural optimization strategy significantly improves the overall service reliability of the battery while maintaining excellent rate performance.

[0106] In some embodiments of the present application, W D4 and W G satisfy the following relationship: 0.6≤W D4 / W G ≤0.9.

[0107] In some embodiments of the present application, W D4 and W G satisfy the following relationship: 0.65≤W D4 / W G ≤0.85.

[0108] In some embodiments of the present application, due to the fact that the grain sizes are not exactly the same, the average value obtained by multiple measurements can better represent the grain anisotropy ratio of the negative active material. The microcrystalline parameter of the negative active material is the arithmetic mean of the parameter values obtained by multiple X-ray diffraction tester test data, wherein the multiple is 3 times or more, such as any value or a range value formed by a range consisting of 3 times, 4 times, 5 times, 6 times, 7 times, 8 times, 9 times, 10 times, 11 times, 12 times, 13 times, 14 times, 15 times, 16 times, 17 times, 18 times, 19 times or 20 times. It is also feasible to exceed 20 times, but for production, the number of measurements increases, which may affect the production efficiency.

[0109] In some embodiments of the present application, based on multiple X-ray diffraction tests, the average value of the plane packing width is obtained by calculating the plane packing width based on the test results of each test respectively; wherein the formula for calculating the plane packing width according to the X-ray diffraction spectrum data is: plane packing width=kλ / (β (110) cosθ (110) ), wherein k is the Scherrer constant, λ is the wavelength of X-ray, β (110) is the half-height width of the graphite carbon (110) crystal face diffraction peak (radian), and θ (110) is the diffraction peak angle corresponding to the graphite carbon (110) crystal face.

[0110] In some embodiments of the present application, the Lc is obtained by averaging the side stacking height calculated based on the result of each test based on multiple X-ray diffraction tests; wherein the formula for calculating the side stacking height according to the X-ray diffraction spectrum data is: side stacking height = kλ / (β (002) cosθ (002) ), wherein k is the Scherrer constant, λ is the wavelength of X-ray, β (002) is the half-height width (in radian) of the (002) crystal plane diffraction peak of graphite carbon, θ (002) is the diffraction peak angle corresponding to the (002) crystal plane of graphite carbon.

[0111] In some embodiments of the present application, the crystallite parameter of the negative electrode active material is obtained by X-ray diffraction tester (XRD) characterization of the negative electrode active material, and analysis and calculation of the obtained XRD data. After XRD tester test, the standard card comparison and analysis are combined with formula calculation.

[0112] In some embodiments of the present application, the X-ray diffraction spectrum includes a spectrum without refinement processing or a spectrum with refinement processing.

[0113] In some embodiments of the present application, the value of k is 0.89. The value of k is related to the determination method of half-height width (FWHM), grain shape and particle size distribution, and is generally 0.87-1. Generally, when β represents half-height width, k is 0.89.

[0114] In some embodiments of the present application, the value of λ is determined by the radiation source of the X-ray spectrometer. If the Cu target is used, the value of λ is (Angstrom), and for the convenience of calculation, it can also be rounded according to the needs, such as rounding to The common radiation source of X-ray spectrometer is Cu target, and the X-ray wavelength of Cu target is 0.154056 nm (i.e. ). Other radiation sources can also be used, and the parameter is determined according to the actual used radiation source.

[0115] In some embodiments of the present application, La and Lc satisfy the following relationship: 1.6≤La / Lc≤2.6.

[0116] Exemplarily, in the present application, the value of La / Lc can be any one of 1.6, 1.61, 1.62, 1.63, 1.64, 1.65, 1.66, 1.67, 1.68, 1.69, 1.7, 1.71, 1.72, 1.73, 1.74, 1.75, 1.76, 1.77, 1.78, 1.79, 1.8, 1.81, 1.82, 1.83, 1.84, 1.85, 1.86, 1.87, 1.88, 1.89, 1.9, 1.91, 1.92, 1.93, 1.94, 1.95, 1.96, 1.97, 1.98, 1.99, 2.0, 2.01, 2.02, 2.03, 2.04, 2.05, 2.06, 2.07, 2.08, 2.09, 2.1, 2.11, 2.12, 2.13, 2.14, 2.15, 2.16, 2.17, 2.18, 2.19, 2.2, 2.21, 2.22, 2.23, 2.24, 2.25, 2.26, 2.27, 2.28, 2.29, 2.3, 2.31, 2.32, 2.33, 2.34, 2.35, 2.36, 2.37, 2.38, 2.39, 2.4, 2.41, 2.42, 2.43, 2.44, 2.45, 2.46, 2.47, 2.48, 2.49, 2.5, 2.51, 2.52, 2.53, 2.54, 2.55, 2.56, 2.57, 2.58, 2.59, 2.6, or a range value group formed by any two thereof.

[0117] In some embodiments of the present application, La and Lc satisfy the following relationship: 1.8≤La / Lc≤2.4.

[0118] The inventors have also found that La (average planar stacking width of a-axis) and Lc (average side stacking height of c-axis) of the graphite material are key parameters for characterizing the order of crystal structure, and both have important influence on the electrochemical performance of the material. Specifically, by optimizing the parameter La value, the number of edge lithium storage sites can be precisely controlled while improving the electron mobility, so as to find the best balance point; keeping La within a reasonable range can avoid the increase of grain boundaries, ensure the smooth diffusion of lithium ions and maintain high initial efficiency. Increasing the value of parameter Lc can not only prolong the lithium intercalation end face to improve the kinetic performance, but also effectively relieve the interlayer stress and inhibit the volume expansion during the cycle process. Through the synergistic optimization of La and Lc, the overall improvement of battery capacity, fast charging performance and cycle stability can be realized, providing key parameter guidance for high-performance battery design.

[0119] In some embodiments of the present application, the calculation formula of the particle size distribution span is as follows: S=(D 90 -D 10 ) / D 50, where D 90 D represents the particle size that accounts for 90% of the cumulative particle size distribution based on volume. 10 D represents the particle size representing 10% of the cumulative particle size distribution based on volume. 50 This indicates the particle size that represents 50% of the cumulative particle size distribution based on volume.

[0120] The inventors discovered that the particle size distribution range of powder reflects the degree of aggregation of active material particles. Corresponding parameters can be obtained by statistically analyzing the particle size frequency of graphite active material powder using a laser particle size analyzer. Reducing the content of fine powder and minimizing active lithium loss due to excessive specific surface area, while controlling the proportion of ultra-large particles to optimize the uniformity of surface defect distribution, can better suppress localized lithium deposition during fast charging. Therefore, regulating the uniformity of particle size distribution can effectively disperse charging and discharging stress, allowing the negative electrode material to maintain structural integrity during long-term cycling, thereby significantly extending battery life.

[0121] In some embodiments of this application, the particle size distribution span satisfies the following relationship: 0.6 ≤ S ≤ 1.7. By controlling the particle size distribution span between 0.6 and 1.7 and optimizing the content of fine powder and large particles through particle size ratio adjustment, the cyclic stress expansion can be better improved, thereby enhancing the fast charge cycle retention rate and storage capacity retention rate.

[0122] Exemplarily, in the present application, the value of the particle size distribution span can be any one of or any range formed by a range of values consisting of 0.6, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.7, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.8, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.0, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.1, 1.11, 1.12, 1.13, 1.14, 1.15, 1.16, 1.17, 1.18, 1.19, 1.2, 1.21, 1.22, 1.23, 1.24, 1.25, 1.26, 1.27, 1.28, 1.29, 1.3, 1.31, 1.32, 1.33, 1.34, 1.35, 1.36, 1.37, 1.38, 1.39, 1.4, 1.41, 1.42, 1.43, 1.44, 1.45, 1.46, 1.47, 1.48, 1.49, 1.5, 1.51, 1.52, 1.53, 1.54, 1.55, 1.56, 1.57, 1.58, 1.59, 1.6, 1.61, 1.62, 1.63, 1.64, 1.65, 1.66, 1.67, 1.68, 1.69, 1.7.

[0123] In some embodiments of the present application, the particle size distribution span satisfies the following relationship: 1≤S≤1.7.

[0124] In some embodiments of the present application, the particle size distribution span satisfies the following relationship: 0.88≤S≤1.36.

[0125] In some embodiments of the present application, the tap density of the negative electrode active material is TD g / cm 3 .

[0126] In some embodiments of the present application, the tap density satisfies the following relationship: 0.8≤TD≤1.2.

[0127] Exemplarily, in the present application, the tap density can be 0.8 g / cm 3 , 0.81 g / cm 3 , 0.82 g / cm 3 , 0.83 g / cm 3 , 0.84 g / cm 30.85g / cm 3 0.86 g / cm 3 0.87g / cm 3 0.88g / cm 3 0.89g / cm 3 0.9g / cm 3 0.91g / cm 3 0.92g / cm 3 0.93g / cm 3 0.94g / cm 3 0.95g / cm 3 0.96g / cm 3 0.97g / cm 3 0.98g / cm 3 0.99g / cm 3 1.0g / cm 3 1.01 g / cm 3 1.02g / cm 3 1.03 g / cm 3 1.04 g / cm 3 1.05g / cm 3 1.06 g / cm 3 1.07g / cm 3 1.08g / cm 3 1.09 g / cm 3 1.1g / cm 3 1.11 g / cm 3 1.12 g / cm 3 1.13 g / cm 3 1.14 g / cm 3 1.15g / cm 3 1.16 g / cm 3 1.17g / cm 3 1.18 g / cm 3 1.19 g / cm 3 1.2g / cm 3 The range is composed of any value in the range or any two of the range values.

[0128] In some specific embodiments of this application, the tap density satisfies the following relationship: 0.85≤TD≤1.18.

[0129] In some other specific embodiments of this application, the tap density satisfies the following relationship: 0.9≤TD≤1.18.

[0130] In some embodiments of the present application, the tap density and the particle size distribution span satisfy the following relationship: TD≥1.1-0.15×S. The constraint relationship between TD and Span is established to ensure the compatibility of high tap density and particle size distribution of the material. When TD≥1.1-0.15×S, the volume expansion of the negative electrode sheet and the lithium consumption in long cycle can be significantly reduced.

[0131] In some embodiments of the present application, the Raman spectrum is subjected to peak separation and fitting processing. The fitting function includes but is not limited to one of Gaussian function, Lorentz function and Voigt function.

[0132] In some embodiments of the present application, the fitting is Gaussian fitting. Gaussian fitting is a commonly used fitting method in the art, that is, fitting according to Gaussian function, or other fitting methods or no fitting can also be used.

[0133] In some embodiments of the present application, the Raman spectrum includes a Raman spectrum subjected to refinement processing. Refinement is a means of mathematical fitting to make the test data as smooth as possible.

[0134] In some embodiments of the present application, the X-ray diffraction spectrum includes a spectrum subjected to refinement processing.

[0135] The above structural characteristic parameters (W D4 , W G , La and Lc) can be directly obtained by measuring data. Since the noise of Raman test and XRD test affects the smoothness of the spectrum, in order to make the test data as smooth as possible, the refinement processing is usually performed in the art. The commonly used software in the art can be used for refinement processing, such as origin, etc. (for XRD data, Jade, etc. can also be used). The universal parameters in the art can be used, and usually no special adjustment is required.

[0136] In some embodiments of the present application, the determination coefficient or fitting goodness R 2 of the curve obtained after refinement or refinement fitting should satisfy: R 2 ≥99%.

[0137] In some embodiments of the present application, the graphite includes at least one of natural flake, artificial graphite sheet, artificial graphite block and artificial graphite ball. The specific type or source of the graphite core is not limited, and various known graphite materials such as traditional natural graphite and artificial graphite can be used.

[0138] In some embodiments of the present application, the carbon coating layer is an amorphous carbon coating layer.

[0139] In some embodiments of the present application, the carbon coating layer contains at least one of hard carbon and soft carbon.

[0140] In some embodiments of the present application, the precursor of the carbon coating layer includes at least one of coal tar pitch, tar pitch, medium temperature coal-based pitch, high temperature coal-based pitch, medium temperature oil-based pitch, high temperature oil-based pitch, phenolic resin, citric acid, glucose and soluble starch. The above-mentioned materials such as coal tar pitch, tar pitch, medium temperature coal-based pitch, high temperature coal-based pitch, medium temperature oil-based pitch, high temperature oil-based pitch, etc. form a soft carbon coating layer after being coated as a precursor. Phenolic resin, citric acid, glucose or soluble starch, etc. form a hard carbon coating layer after being coated as a precursor.

[0141] In the present application, the negative active material is obtained by grading and screening a commercial negative material, and can be prepared by a universal method without particular limitation.

[0142] According to the second aspect of the embodiments of the present application, a negative electrode sheet is provided, which includes a current collector and a coating layer arranged on at least one side surface of the current collector, and the raw material for preparing the coating layer includes the above-mentioned negative active material.

[0143] The composition of the negative current collector is not particularly limited in the present application, and it can be selected from the negative current collectors commonly used in the art, such as copper foil.

[0144] In the present application, the negative electrode sheet can be prepared by various methods known in the art. For example, a negative electrode slurry containing a negative material, a conductive agent and a binder is first prepared, the negative electrode slurry is coated on a negative current collector, and after drying and other processes, a negative electrode sheet is obtained.

[0145] In some specific embodiments of the present application, the method for preparing the negative electrode sheet includes the following steps:

[0146] The negative active material, the conductive agent, the thickening agent, the binder, the toughening agent and water are mixed to prepare a slurry, and a negative electrode slurry is obtained;

[0147] The negative electrode slurry is coated on at least one side surface of the negative current collector, and after drying and rolling, a negative electrode sheet is obtained.

[0148] In the present application, the type of conductive agent is not particularly limited, and it can be selected from the conductive agents commonly used in the art, including but not limited to at least one of graphene, conductive carbon black, carbon fiber and carbon nanotube.

[0149] In the present application, the type of thickening agent is not particularly limited, and it can be selected from the thickening agents commonly used in the art, including but not limited to at least one of sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA) and hydroxypropyl methyl cellulose (HPMC).

[0150] In the present application, the type of the binder is not particularly limited, and it can be selected from the binders conventionally used in the art, including but not limited to at least one of styrene butadiene rubber (SBR), polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), and polyurethane.

[0151] In the present application, the type of the toughening agent is not particularly limited, and it can be selected from the toughening agents conventionally used in the art, including but not limited to at least one of N-methyl pyrrolidone (NMP), acrylonitrile-butadiene-styrene copolymer (PTC), and butadiene (BD).

[0152] In some embodiments of the present application, the mass fractions of the negative electrode active material, the conductive agent, the thickening agent, the binder, and the toughening agent are 96-98, 0.1-1, 0.8-1.8, 0.5-1.5, and 0.1-1, respectively.

[0153] For example, in the present application, the mass fractions of the negative electrode active material, the conductive agent, the thickening agent, the binder, and the toughening agent are 96.8%, 0.5%, 1.2%, 1%, and 0.5%, respectively.

[0154] In the present application, the drying process is not particularly limited, and it can be a baking drying process or the like conventionally used in the art.

[0155] In some embodiments of the present application, the preparation method further comprises a step of die cutting after rolling.

[0156] In some embodiments of the present application, the solid content of the negative electrode slurry is 30-65 wt%.

[0157] For example, in the present application, the solid content of the negative electrode slurry can be any value selected from 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, or a range formed by any two of the values.

[0158] In some embodiments of the present application, the viscosity of the negative electrode slurry is 1000-8000 mPa·s at room temperature, and the room temperature is 25±2℃.

[0159] Exemplarily, in the present application, the viscosity of the negative electrode slurry at room temperature can be in the range consisting of any one value or a range value formed by any two values selected from the group consisting of 1000 mPa s, 1500 mPa s, 2000 mPa s, 2500 mPa s, 3000 mPa s, 3500 mPa s, 4000 mPa s, 4500 mPa s, 5000 mPa s, 5500 mPa s, 6000 mPa s, 6500 mPa s, 7000 mPa s, 7500 mPa s, 8000 mPa s.

[0160] In some embodiments of the present application, the single-side thickness of the negative electrode tab coating layer is 0.05-0.30 mm.

[0161] Exemplarily, in the present application, the single-side thickness of the negative electrode tab coating layer can be in the range consisting of any one value or a range value formed by any two values selected from the group consisting of 0.05 mm, 0.10 mm, 0.15 mm, 0.20 mm, 0.25 mm, 0.30 mm.

[0162] In some embodiments of the present application, the unit area mass of the negative electrode tab coating layer is 80-200 g / m 2 .

[0163] Exemplarily, in the present application, the unit area mass of the negative electrode tab coating layer can be in the range consisting of any one value or a range value formed by any two values selected from the group consisting of 80 g / m 2 , 90 g / m 2 , 100 g / m 2 , 110 g / m 2 , 120 g / m 2 , 130 g / m 2 , 140 g / m 2 , 150 g / m 2 , 160 g / m 2 , 170 g / m 2 , 180 g / m 2 , 190 g / m 2 , 200 g / m 2 .

[0164] In some embodiments of the present application, the compacted density of the negative electrode tab coating layer is 1.30-1.75 g / cm 3 .

[0165] Exemplarily, in the present application, the compacted density of the negative electrode tab coating layer can be in the range consisting of any one value or a range value formed by any two values selected from the group consisting of 1.30 g / cm 3 , 1.35 g / cm 3 , 1.40 g / cm 3 , 1.45 g / cm3 1.50 g / cm 3 1.55 g / cm 3 1.60 g / cm 3 1.65 g / cm 3 1.70 g / cm 3 1.75 g / cm 3 1.80 g / cm

[0166] According to a third embodiment of the present application, a secondary battery is provided, the secondary battery comprising a positive electrode sheet, a negative electrode sheet, and a separator film, the separator film being located between the positive electrode sheet and the negative electrode sheet, the negative electrode sheet being the above-mentioned negative electrode sheet.

[0167] Optionally, the secondary battery can be a lithium ion battery, but is not limited thereto, and the battery can also be a sodium ion battery, a magnesium ion battery, etc.

[0168] It should be noted that the present application does not have special restrictions on the types or specific components of the positive electrode sheet, the electrolyte, the separator film, etc., as long as the purpose of the present application can be achieved.

[0169] According to a fourth aspect embodiment of the present application, a power consuming device is provided, the power consuming device comprising the above-mentioned secondary battery.

[0170] In some specific embodiments of the present application, the power consuming device is an electric vehicle. It can also be other power consuming devices such as energy storage systems, electric tools, unmanned aerial vehicles, mobile devices such as wearable products, notebook computers, mobile phones, etc.

[0171] In some specific embodiments of the present application, the power consuming device is an electric vehicle or an electric bicycle. It can also be other electric vehicles such as electric motorcycles, electric scooters, electric wheelchairs, etc.

[0172] The content of the present application is further described in detail below through specific embodiments.

[0173] The powder physical property characterization test method of the negative electrode active material in the following examples and comparative examples includes the following steps:

[0174] 1. Carbon-coated layer edge defect active W D4 / W G Characterization:

[0175] The Raman spectrum was obtained by fine scanning of the negative electrode active material structure using a laser confocal Raman spectrometer (LabRAM Odyssey, HORIBA, France). A small amount of powder sample was placed in the center of the sample groove and flattened with a glass sheet. The laser wavelength was 532 nm, and the laser output power was ≥ 90 mW. The Raman data were refined and analyzed, and then fitted by mathematical means (Gaussian peak fitting). The fitting curve after refinement met: R 2 ≥ 99%). The D4 peak is located at 1180 cm -1 , the G peak is located at 1580 cm -1 , W D4 is the D4 peak half-width, W G is the G peak half-width, and the ratio of the two is the edge defect activity of the carbon coating layer.

[0176] 2. Graphite intrinsic body crystallite parameter - grain anisotropy ratio La / Lc characterization:

[0177] The diffraction spectrum of the graphite active material was obtained by XRD diffractometer (D8 Advance, Bruker, Germany). The powder sample was uniformly dispersed on the surface of an optical glass plate, and the sample parameters were adjusted. X-ray diffraction technology is a technology for analyzing crystal structure and phase characteristics by using X-ray diffraction in crystal materials. In this study, a German Bruker D8 Advance powder X-ray diffractometer was used. The sample parameters were as follows: Cu target (λ = 0.1541 nm), working voltage 40 kV, working current 40 mA, scanning range 5-80°, step size 0.02°. The XRD spectrum was obtained, and then the diffraction spectrum was refined (the refined curve meets: R 2 ≥ 99%), and standard card comparison was performed to obtain the diffraction angle θ and peak half-width β of the graphite carbon (002) crystal face diffraction peak (near 26.5°) and graphite carbon (110) crystal face diffraction peak (near 44.5°). The plane packing width and side packing height were calculated by the Bragg equation and the Scherrer formula, respectively. The number of test samples was 10, and the arithmetic mean value was taken to calculate the average plane packing width (La) and average side packing height (Lc), which were the crystallite parameters of the graphite.

[0178] The calculation formulas of the plane packing width and the side packing height are as follows: Plane packing width = kλ / β (110) cosθ (110) , where θ (110) is the graphite carbon (110) diffraction peak angle, β (110) is the graphite carbon (110) crystal face diffraction peak half-width (radian), and λ is the wavelength of X-ray (0.1541 nm, i.e. ) ; k is Scherrer constant (0.89) ; side stacking height = k l / b (002) cos q (002) , q (002) is the graphite carbon (002) crystal face diffraction peak angle, b (002) is the graphite carbon (002) crystal face diffraction peak half-height width (radian system), and l is the wavelength of X-ray (0.1541 nm, i.e. ) ; k is Scherrer constant (0.89).

[0179] 3. Particle size distribution span (Span) characterization:

[0180] By using a laser diffraction particle size analyzer (MS3000), the sample particles are dispersed in a liquid medium at a concentration of 200-300 mg / L, and a monochromatic light beam is passed through it. After the light is scattered by the particles, it is distributed at different angles, and the values of the scattering diagram received by the regular multi-detector at many angles are recorded for analysis. Using the Rayleigh scattering formula, the scattering values are calculated to obtain the ratio of the volume of each particle size level to the total volume, thereby obtaining the volume distribution of the particle size. The calculation formula is S = (D 90 -D 10 ) / D 50 , D 90 represents the particle size of 90% in the cumulative particle size distribution based on volume, D 10 represents the particle size of 10% in the cumulative particle size distribution based on volume, and D 50 represents the particle size of 50% in the cumulative particle size distribution based on volume. The particle size distribution span can reflect the concentration of graphite particles.

[0181] 4. Tap density TD characterization:

[0182] TD is the tap density of the graphite active material. According to the national standard GB / T5162-2021 "Determination of tap density of metal powder", the tap density of the negative electrode active material is calculated by the formula p = m / V after 3000 times of vibration using the FT-100E type tap density instrument.

[0183] Example 1

[0184] This example provides a negative electrode active material, a negative electrode sheet and a secondary battery. The negative electrode active material includes a graphite core and an amorphous carbon coating layer covering at least part of the surface of the graphite core, and the scanning electron microscope image thereof is as shown in Figure 2 . The material is obtained by grading and screening the commercially purchased negative electrode active material, and is characterized by Raman spectrum, XRD and particle size distribution, and the results are as shown in Figures 3 to 5 . The physical property parameters used to calculate CPI in the specific test results are shown in Table 1.

[0185] The process for preparing the negative electrode sheet using the negative active material described above is as follows:

[0186] The negative active material obtained by screening is used to prepare a negative electrode slurry, and the mass percentage of active material, conductive agent, thickening agent, binder, and toughening agent in the negative electrode slurry is 96.8%, 0.5%, 1.2%, 1.0%, and 0.5%. The specific preparation method of the negative electrode slurry is as follows: the negative active material, deionized water, conductive agent (conductive carbon black), binder (PVDF), thickening agent (CMC), and toughening agent (NMP) are added to a stirring tank, the rotational speed is selected to be 25 r / min, and stirring is performed for 2 h to form a mixed negative electrode slurry. The negative electrode slurry is uniformly coated on both sides of the negative current collector copper foil, dried in an oven, and then subjected to cold pressing and slitting to obtain a negative electrode sheet.

[0187] Further, the process for preparing a lithium ion secondary battery using the negative electrode sheet described above is as follows:

[0188] The positive active material LiNi 0.8 Co 0.1 Mn 0.1 O, conductive agent (conductive carbon black), and binder (polyvinylidene fluoride) are uniformly mixed in an appropriate amount of solvent NMP (N-methyl-2-pyrrolidone) at a mass ratio of 96:2:2 to obtain a positive electrode slurry. The positive electrode slurry is uniformly coated on both sides of the positive current collector aluminum foil, and then dried, rolled, and die-cut to obtain a positive electrode sheet.

[0189] Vinyl carbonate (EC), methyl ethyl carbonate (EMC), and diethyl carbonate (DEC) are mixed at a volume ratio of 1:1:1 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent at a concentration of 1 mol / L, and a fully dissolved electrolyte is obtained.

[0190] A polyethylene film with an aluminum oxide coating obtained by commercial purchase is selected as a separator film.

[0191] The negative electrode sheet, positive electrode sheet, electrolyte, and separator film obtained by the above operations are assembled into a lithium ion battery, and the specific process is as follows: the positive electrode sheet, separator film, and negative electrode sheet are stacked in order, with the separator film between the positive and negative electrode sheets, and then wound to obtain a bare cell; the bare cell is placed in an outer packaging shell, dried, and then injected with electrolyte. After vacuum packaging, standing, formation, shaping, and other processes, a lithium ion battery is obtained.

[0192] Example 2-8 and Comparative Example 1

[0193] It is substantially same as Example 1, the only difference is that the physical property parameters of the negative active material are different, see Table 1 for details.

[0194] Table 1

[0195] [WC D4 / cm -1 ]]> [CATALOGUE G / cm -1 ]]> [CDATAW D4 / W G ]]> La / nm Lc / nm La / Lc D 10 / μm D 50 / μm D 90 / μm S TD / g / cm 3 ]]> CPI Example 1 151 161 0.94 77.4 43.5 1.78 7.8 18.6 34.5 1.44 1.01 2.27 Example 2 110 172 0.64 79.1 44.1 1.79 7.9 16.8 31.9 1.43 0.99 1.85 Example 3 85 143 0.59 76.3 40.7 1.87 8.5 13.7 31.8 1.70 1.15 1.96 Example 4 140 164 0.85 73.5 27.5 2.67 6.7 14.7 31.5 1.69 0.92 3.41 Example 5 136 159 0.86 74.5 37.6 1.98 10.1 15.3 25.6 1.01 0.98 2.13 Example 6 87 165 0.53 73.5 45.6 1.61 9.9 14.7 26.8 1.15 1.05 1.39 Example 7 48 150 0.32 77.8 46.1 1.69 10.2 14.8 26.7 1.11 0.99 1.09 Example 8 118 165 0.72 72.5 35.6 2.04 8.1 17.9 36.7 1.60 0.82 2.33 Comparative Example 1 141 167 0.84 71.5 27.5 2.6 6.5 17.9 46.7 2.25 0.97 3.65

[0196] The performance of the lithium ion batteries prepared in the above examples and comparative examples was tested by the following method:

[0197] 1. Lithium precipitation test: after the lithium ion batteries prepared in the examples and comparative examples were repeatedly charged at 5C rate and discharged at 1C rate for 10 times at 25℃, the lithium ion batteries were fully charged at 5C rate, then the negative electrode sheet was disassembled and the lithium precipitation on the surface of the negative electrode sheet was observed. Among them, the lithium precipitation area on the surface of the negative electrode sheet <10% is counted as slight lithium precipitation, the lithium precipitation area 10-50% is counted as moderate lithium precipitation, and the lithium precipitation area >50% is counted as severe lithium precipitation.

[0198] 2. Normal temperature cycle performance test: at 25℃, the lithium ion batteries prepared in the examples and comparative examples were charged at an equivalent of 4C rate and discharged at 1C rate, and the full charge and full discharge cycle test was carried out, and the 1000cls capacity retention rate was recorded.

[0199] 3. Lithium ion battery full charge expansion rate test: at room temperature (25℃), the thickness of the above lithium ion battery at 100% SOC was tested by using a screw micrometer, and recorded as T0; then after 1C charging / 1C discharging cycle to 500cls, the thickness of the lithium ion battery at 100% SOC was tested, and recorded as T1, then the full charge lithium ion battery expansion rate was (T1-T0) / T0*100%.

[0200] The lithium precipitation test results of the sample of Example 1 scheme are shown in Figure 6 The lithium precipitation test results of the sample of Comparative Example 1 scheme are shown in Figure 7 As can be seen from Figure 6 , the negative electrode sheet of Example 1 does not appear lithium precipitation. As can be seen from Figure 7 , the negative electrode sheet of Comparative Example 1 appears severe lithium precipitation.

[0201] The performance test results of the lithium ion batteries in the above examples 1 to 8 and comparative example 1 are shown in the following Table 2.

[0202] Table 2

[0203] Analysis of lithium deposition interface 4C cycle retention / % Electrode expansion rate / % Example 1 No lithium deposition 90.5% 14.0% Example 2 No lithium deposition 90.9% 13.6% Example 3 No lithium deposition 91.3% 13.6% Example 4 No lithium deposition 89.1% 15.2% Example 5 No lithium deposition 91.3% 13.2% Example 6 No lithium deposition 89.9% 12.9% Example 7 Slight lithium deposition 85.1% 17.1% Example 8 Slight lithium deposition 90.1% 16.8% Comparative Example 1 Severe lithium deposition 70.2% 20.5%

[0204] As can be seen from the above table, when the carbon-coated index (CPI) of the graphite negative active material is controlled in the interval of 0.7-3.64, the lithium ion battery dynamics exhibits excellent electrochemical performance, which can simultaneously have good cycle life and low volume expansion. The comprehensive performance advantage is derived from the multi-scale synergistic regulation strategy designed in the application: 1) a relatively ideal carbon-coated layer structure: a synergistic structure with a reasonable interlayer spacing, long-range order and short-range disorder, and an active edge defect (W D4 / W G ), which helps to provide abundant lithium intercalation active sites; 2) optimization of crystallite orientation: a suitable grain anisotropy ratio, which helps to reduce the lithium ion diffusion energy barrier; 3) concentrated particle size distribution: the active material powder has a narrow particle size distribution (low Span value), which reduces the proportion of fine powder and large particles, which helps to achieve good grading between particles, improve the tap density, and at the same time, reduce the electrode expansion rate, and avoid the negative effects of fine powder (excessive electrolyte decomposition caused by high specific surface area) and large particles (long intercalation path leading to fast charging lithium precipitation). The application cleverly defines a composite performance index (CPI = (W D4 / W G ) 0.55 × (La / Lc) × (S / 0.65) 0.35 ) to synergistically regulate the three key structural parameters, so that the material exhibits: 1) high lithium extraction / intercalation kinetics, only slight lithium precipitation or even no lithium precipitation occurs during the lithium precipitation test process; 2) fast charging cycle capacity retention rate is also significantly improved; 3) the intercalation degree of the material is reduced; 4) the extreme disorganized structure and ineffective intercalation structure are reduced, effectively avoiding the loss of active lithium and active material caused by excessive electrolyte decomposition at high temperature.

[0205] When CPI is too low (less than 0.7), the carbon-coated layer edge defect activity is low, the disordered structure and defect density are insufficient, which easily leads to Li + migration energy barrier, poor kinetics, easy lithium precipitation in fast charging cycle, and significant capacity retention and interface deterioration; and when CPI is too high (more than 3.64), the intercalation end surface is insufficient and the particle size distribution is too wide, which also leads to significant performance deterioration, limited intercalation sites, concentrated Li + insertion at high current density, causing excessive local stress and material crushing, high cell expansion rate; rich in fine powder and large particles, resulting in a wide particle size distribution, causing active lithium loss, and damaging kinetics and cycle performance. Further, as can be seen from Comparative Example 8 and Example 1, when TD and Span satisfy TD≥1.1-0.15×S, the compatibility of high tap density and concentrated particle size distribution can be better ensured, and materials satisfying the above relationship are less likely to have problems such as demolding, interface deterioration or cycle retention loss during the cycle process.

[0206] In summary, the negative active material of the scheme of the application is designed by synergistically regulating the edge defect activity density (W D4 / W G ), the microcrystalline parameter-grain anisotropy ratio (La / Lc) and the powder particle size distribution span of the carbon coating layer, to obtain a high-performance fast-charging type long-cycle graphite negative electrode material. By constructing the graphite negative electrode material meeting the above multi-dimensional parameter requirements, a lithium ion battery negative electrode with high deintercalation / intercalation lithium kinetic performance, excellent cycle performance and low expansion characteristics can be obtained, which meets the rapid selection requirements of the negative active material for the battery factory.

[0207] The above has made a detailed description of the embodiments of the application, but the application is not limited to the above embodiments, and various changes can be made within the knowledge range of ordinary skilled persons in the art without departing from the purpose of the application.

Claims

1. A negative electrode active material, characterized by: The graphite core and a carbon coating layer covering at least part of the surface of the graphite core; The negative active material has a carbon characteristic peak in a Raman spectrum, the carbon characteristic peak includes a D4 peak with a peak shift of 1160 to 1200 cm -1 and a G peak with a peak shift of 1560 to 1600 cm -1 in the peak separation processing, a half-height width of the D4 peak is W D4 , and a half-height width of the G peak is W G . The average planar stacking width of the negative electrode active material is La, and the average lateral stacking height is Lc. The span of the particle size distribution of the negative electrode active material is S. The comprehensive performance parameter of the negative electrode active material is CPI. The W D4 , W G , La, Lc, S and CPI satisfy the following relationship: CPI = (W D4 / W G ) 0.55 × (La / Lc) × (S / 0.65) 0.35 ; The value of the CPI satisfies the following relationship: 0.7≤CPI≤3.

64.

2. The negative active material according to claim 1, characterized by: The value of the CPI satisfies the following relationship: 1.38≤CPI≤3.

42.

3. The negative active material according to claim 1, characterized in that: The W D4 With W G satisfies the following relationship: 0.3≤W D4 / W G ≤1.

4. The negative active material according to claim 1, characterized by: The La and Lc satisfy the following relationship: 1.6≤La / Lc≤2.

6.

5. The negative active material of claim 1, wherein: The span of the particle size distribution satisfies the following relationship: 0.6≤S≤1.

7.

6. The negative active material of claim 1, wherein: The tap density of the negative active material is TD g / cm 3 The tap density and the particle size distribution span satisfy the following relationship: TD≥1.1-0.15×S.

7. The negative active material of claim 1, wherein: The Raman spectrum is subjected to peak separation and fitting, and the fitting includes Gaussian fitting.

8. A negative electrode sheet characterized by comprising: The negative electrode plate includes a current collector and a coating layer arranged on at least one side surface of the current collector, and the preparation raw material of the coating layer includes the negative electrode active material according to any one of claims 1 to 7.

9. A secondary battery characterized by comprising: The secondary battery includes a positive electrode plate, a negative electrode plate, and a separator, the separator is located between the positive electrode plate and the negative electrode plate, and the negative electrode plate is the negative electrode plate according to claim 8.

10. An electrical device, characterized by: The electric device includes the secondary battery according to claim 9.

Citation Information

Patent Citations

  • Negative pole piece and preparation method thereof, lithium ion battery and electric equipment

    CN114824226A

Cited By

  • Battery monomer, battery device, energy storage device and power utilization device

    CN122291410A